Needs analysis for developing an inquiry - based learning instructional module on the topic of gravitation for secondary schools - Awang Zaini, Nourhaizum; Razali, Fazilah; Mohd Ayub, Ahmad Fauzi (Journal of Islamic, Social, Economics and Development, 2025)
This is a need analysis study in the first stage of Design and Develop Research (DDR). The purpose of this study was to identify the needs on developing Inquiry Based Learning (IBL) instructional module on Gravitation topic for secondary school in Malaysia. The study was done qualitatively using a semi-structured interview method with four physics teachers chosen through a purposive sampling technique. The data was analysed using thematic analysis, and the results were displayed as thematic maps. The study discovered four major themes:(1) the significance of learning gravitation topic, (2) Issues in teaching and learning gravitation topic, (3) applied instructional strategies in gravitation topic, and (4) Desired enhancement for instructional strategies in gravitation topic. The study's findings suggest that IBL instructional module for Gravitation topic is required. This module has the potential to establish a student-centered learning environment that includes the key elements of 21st century learning: critical thinking, creativity, communication, and values. Furthermore, teachers can modify the instructional approaches utilised in the classroom to teach the concept of gravitation by guiding module development. Teachers can also refine their instructional methods for teaching the concept of gravitation by referring to the developed module.